(untitled) (South Asian Journal of Agriculture, 2025)
Recent research on biochar mainly heeds its use in climate-related studies, immobilizing contaminant, mending soil, restoring nutrient, and treating wastewater. The tangible attributes of biochar improving plant growth and fertilizer use efficiency has become orthodox in enormous studies. Meager cost, excessive porosity, ample surface area, renewability and customizable chemistry hold promise for various engineering applications, some of which need further contemplation. This review successively quests the compatibility of biochar as a potent carrier material to allot agrochemicals and microbes. It enlightens crucial specifications for evaluating biochar’s potential as a delivery agent, including its physicochemical properties, adsorption and release mechanisms of agrochemicals and microbes, long-term effects as well as economic and environmental benefits. The review concludes with a brief discussion on how nano-interventions could enrich biochar properties for effective delivery applications. South Asian J. Agric., Vol. 11, No.1, 2025: 8-23